Fabrication of polymeric composite GTR membrane from eggshell powder, polylactic acid and polyethylene glycol for periodontal application: in vitro evaluation - Farman, Humaira; Khan, Muhammad Adnan; Alamoudi, Abdulmohsin J.; Sharif, Faiza; Alshamrani, Meshal; Liaqat, Saad; Rizg, Waleed Y.; Shaik, Rasheed A.; Muhammad, Nawshad (Frontiers in Materials, 2023)
This study aims to fabricate, characterize and evaluate Guided tissue regeneration (GTR) membrane novelcontaining eggshell (ES), and cChlorhexidine (CHX) and polymeric matrix for periodontal application. incorporated GTR membrane and to evaluate their mechanical and physical properties along with their antibacterial potential and biocompatibility. ES powder ground to size 74 µm was mixed in the PLA and PEG Polylactic Acid (PLA) and Polyethylene Glycol (70:30 ratios) mixture in 10% and 30% wt to fabricate the membrane and named it groups C-10 and C-30. Along with this, 0.25% and 0.5% chlorhexidine gluconate (CHX) powder were adsorbed on ES powder and incorporated in PLA and PEG mixture to fabricate drug containing groups C-10CHX and C-30CHX respectively. Analytical techniques were used to characterize the ES and its composite membrane. FTIR analysis confirmed the presence of ES powder and CHX in the experimental groups. SEM showed conglomerated appearance with voids in the fabricated GTR membranes. UTM was used to measure tensile strength, Young's Modulus, and percent elongation of the prepared GTR membrane. Experimental groups containing 10% ES powder (C-10 and C-30) had adequate tensile properties. The percent mass change of the samples was calculated by the change in weight of the samples (W d ) from the weight of samples after immersion in phosphate phosphate-buffered saline PBS (W t ). Contact angle measurement showed that all membranes were found to be hydrophilic (contact angle<90). The antibacterial potential of the specimens were determined by disc diffusion method. Groups containing the drug CHX (C-10CHX and C-30CHX) had significant disc diffusion antibacterial activity. Cell viability assay of the ES powder and the GTR membranes werewas carried out by Alamar Blue Assay using mouse fibroblasts NIH3T3 and pre-osteoblasts that indicated very good biocompatibility of the groups (C, C-10, C-30, and C-10CHX) while experimental group C-30CHX showed slight cytotoxicity (Cell Viability >70%).